Lokusi dan Ilokusi dalam Terjemahan Al-Quran Surah Ar-Rahman - Aisyah, A. (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
This research examines locution and illocution in the translation of the Al-Quran Surah Ar-Rahman. This research aims (1) to describe the locutions contained in the translation of the Al-Quran surah Ar-Rahman as a form of learning in the field of pragmatics and (2) to describe the illocutions contained in the translation of the Al-Quran surah Ar-Rahman as a form of learning in the field of pragmatics . The data in this research is the translation of the 55th surah of the Al-Quran, namely, Surah Ar-Rahman which consists of 78 verses, but then it is focused on the translation of verses related to Allah's pleasure or the mercy of Allah SWT, which are contained in the translated Mushaf of the Al-Quran. This research is included in the type of qualitative research which is descriptive in nature. Data analysis techniques are carried out using identification techniques, wording techniques, classification techniques, description techniques, discussion techniques and data conclusions that have been discussed. The conclusions in this research are (1) the locutions contained in the translation of the Koran Surah Ar-Rahman related to the verses that discuss Allah's mercy consisting of imperative locutions, declarative locutions and interrogative locutions and (2) the use of illocutions found in the translation Quran Surah Ar-Rahman, consists of assertive illocution, directive or competitive illocution, commissive and expressive illocution, and conflict (conflict).